Influence of geographical latitude on vitamin D status: cross-sectional results from the BiomarCaRE consortium. Issue 11 (14th December 2022) - Oskarsson, Viktor; Salomaa, Veikko; Reinikainen, Jaakko; Männistö, Satu; Palmieri, Luigi; Donfrancesco, Chiara; Sans, Susana; Costanzo, Simona; de Gaetano, Giovanni; Iacoviello, Licia; Veronesi, Giovanni; Ferrario, Marco M.; et al.
Abstract: Even though sunlight is viewed as the most important determinant of 25-hydroxyvitamin D (25(OH)D) status, several European studies have observed higher 25(OH)D concentrations among north-Europeans than south-Europeans. We studied the association between geographical latitude (derived from ecological data) and 25(OH)D status in six European countries using harmonised immunoassay data from 81 084 participants in the Biomarkers for Cardiovascular Risk Assessment in Europe (BiomarCaRE) project (male sex 48·9 %; median age 50·8 years; examination period 1984–2014). Quantile regression models, adjusted for age, sex, decade and calendar week of sampling and time from sampling to analysis, were used for between-country comparisons. Up until the median percentile, the ordering of countries by 25(OH)D status (from highest to lowest) was as follows: Sweden (at 65·6–63·8°N), Germany (at 48·4°N), Finland (at 65·0–60·2°N), Italy (at 45·6–41·5°N), Scotland (at 58·2–55·1°N) and Spain (at 41·5°N). From the 75th percentile and upwards, Finland had higher values than Germany. As an example, using the Swedish cohort as a comparator, the median 25(OH)D concentration was 3·03, 3·28, 5·41, 6·54 and 9·28 ng/ml lower in the German, Finnish, Italian, Scottish and Spanish cohort, respectively ( P -value < 0·001 for all comparisons). The ordering of countries was highly consistent in subgroup analyses by sex, age, and decade and season of sampling. In conclusion, we confirmed the previous observation of a north-to-south gradient of 25(OH)D status in Europe, with higher percentile values among north-Europeans than south-Europeans.